Review of Ex Post Assessments and Issues Relating to the Policy on Longer-Term Program Engagement. (Policy Papers; Policy Paper ;, 2006)
This review assesses the experience gained to date in carrying out the longer-term program engagement (LTPE) policy and preparing the ex post assessments (EPAs). It discusses the main characteristics of LTPE members and the findings of the EPAs, analyzes the role of the EPAs in the Fund's due diligence, and provides recommendations for improving their effectiveness.